Refashioning Commodities: Women and the Sourcing of Secondhand Clothing in the Philippines - Milgram, B. Lynne (Anthropologica, 2022)
Since the mid-1990s, the increasing export of the West's used clothing to southern regions may initially appear to be another marker of northern exploitation. But to consider the southern flow of this commodity in such terms sees people as passive recipients of global commodity chains and overlooks the alternatives they create in dress and work practice. Focussing on women's roles in the secondhand clothing industry in the Philippines, this paper argues that traders and consumers reconfigure the logic of the market and the meaning of this transnational commodity by incorporating cultural practices into a global trade marginal to state influence. By dialectically engaging this commodity across diverse cultural and economic spheres, women dissolve assumptions of fixed dichotomies and dominance to reconceptualize global processes from a gendered perspective and as multiple and ongoing.